Glycol chitosan in situ coating on PLGA nanoparticle curtails extraneous paclitaxel precipitates and imparts protein corona independent hemocompatibility. (1st June 2020) - Kaur, Navneet; Mathur, Purvi; Yadav, Pranjali; Chakraborty, Swaroop; Shanavas, Asifkhan
Graphical abstract: Highlights: We studied high and low molecular weight PLGA nanoparticles with glycol chitosan and carboxymethyl chitosan coating. Glycol chitosan reduced Extraneous Paclitaxel Precipitates (EPPs) during LMW PLGA nanoprecipitation for uniform intra cellular drug delivery. Molecular weight wise composition of protein corona varied distinctly between glycol chitosan and carboxymethyl chitosan coatings. Glycol chitosan coated nanoparticles fared better in terms of compatibility with RBC in its nascent form irrespective of its positive charge. Abstract: Poly (lactide-co-glycolide) (PLGA) nanoparticles surface functionalized with water soluble glycol chitosan (GC) and carboxymethyl chitosan (CMC) has been studied for their drug (Paclitaxel and Doxorubicin) loading, yield, cellular uptake, serum protein adsorption and hemocompatibility. It was observed that Paclitaxel (Ptxl) phase out as Extraneous Ptxl Precipitates (EPP) (>25 %) in case of uncoated and CMC coated low molecular weight (LMW) PLGA nanoparticles (PNPs). The EPP formation was significantly reduced to ∼5 % with GC coating as it enhanced LMW PLGA precipitation and yield predominantly spherical polymeric nanoparticles towards better encapsulation of Ptxl and thus uniform intracellular drug distribution. Interestingly, protein corona analysis showed cmcPNPs and gcPNPs to be distinct from each other in associating mainly with serum proteins of molecular weight < 30 kDa and >30 kDa respectively. While CMC functionalization showed >10 % hemolysis, at similar concentration GC coating was found to provide superior hemocompatibility even in the absence of protein corona.